Analisis Pengaruh Artificial Intelligence Berbasis Images Preprocessing dalam Implementasi Deteksi Kematangan Buah Tomat - Sevia Dwi Yanti; Hikmah Rahma; Nur Aziezah; Ridwan Siskandar; Aep Setiawan (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
Technological developments continue to increase not only in the industrial sector, but have also spread to the agricultural sector, including the tomato farming process. Currently, the stage of harvesting tomatoes no longer relies on manual work, but instead utilizes artificial intelligence technology based on images preprocessing. This research aims to see whether the independent variable (AI effectiveness) has an influence on the dependent variable (tomato ripeness level). The method used is qualitative with simple linear regression data analysis techniques which include the t test and f test. The sample used was a random sampling technique with data collection by distributing questionnaires to a total of 48 respondents. The research results show that the effectiveness of AI has a positive effect on the level of ripeness of tomato fruit. This can be proven from a simple linear regression analysis to obtain the equation Y = 3.498 + 0.787X. The findings from the ttest show that tcount (7.644) > ttable (2.012) with a significance of 0.001 < 0.05. Therefore, the conclusion drawn is to accept the alternative hypothesis (H1) while rejecting the null hypothesis (H0).